Changes in chemical coding of myenteric neurones in ulcerative colitis. Issue 1 (1st January 2003) - Neunlist, M; Aubert, P; Toquet, C; Oreshkova, T; Barouk, J; Lehur, P A; Schemann, M; Galmiche, J P
Abstract : Background: Morphological and functional changes in the enteric nervous system (ENS) have been reported in inflammatory bowel diseases but it is still uncertain whether neurochemical coding of myenteric neurones is altered in ulcerative colitis (UC). Aims: In this study we investigated transmitter co-localisation in myenteric neurones of normal colon and the colon of patients with UC. Methods: Choline acetyltransferase (ChAT), neurone specific enolase (NSE), vasoactive intestinal peptide (VIP), and substance P (SP) were detected by immunohistochemical methods in whole mounts of colonic myenteric plexus of UC patients (n=10) and controls (n=8). Results: The proportion of ChAT positive and VIP positive neurones relative to the NSE population did not differ in inflamed (33.3% and 9.3%, respectively) and non-inflamed segments (33.6% and 9.7%) of UC colon compared with controls (35.0% and 6.9%). The proportion of SP positive neurones was significantly larger in both inflamed (15.5%) and non-inflamed (20.3%) segments than in controls (5.9%). Analysis of changes in subpopulations showed that 26.9% of neurones were only ChAT positive in controls but that the proportion was significantly smaller in inflamed (18.8%) and non-inflamed (15.8%) areas of UC. The proportions of neurones containing ChAT and SP were significantly higher in inflamed (11.8%) and non-inflamed (13.9%) areas than in controls (5.0%). Conclusion: Remodelling of myenteric neurones in UC involves a shift from mainly cholinergic to more SP positive innervation. This effect may constitute part of the neuronal basis for the motility disturbances observed in UC.